Acute lead arsenate poisoning in beef cattle in Uruguay. (March 2019) - Schild, Carlos O.; Giannitti, Federico; Medeiros, Rosane M. T.; da Silva Silveira, Caroline; Caffarena, Rubén D.; Poppenga, Robert H.; Riet-Correa, Franklin
We describe and illustrate lesions in an outbreak of lead arsenate poisoning in beef cattle that ingested pesticide residues stored in an abandoned building of a former orange orchard. Of 70 exposed cattle, 14 had diarrhea, paresis, ataxia, recumbency, and/or seizures. Ten of the affected animals died after a clinical course of 12–18 h. Pathologic findings in 3 steers included extensive necrohemorrhagic, ulcerative rumenitis, omasitis, and abomasitis; lymphocytolysis in lymphoid organs; and nephrosis. Hepatic arsenic and lead levels in cases 1–3 were 20, 24, and 31 ppm, and 8.3, 25, and 9.4 ppm, respectively. Lesions in the forestomachs and lymphoid tissues have been rarely reported in cases of lead arsenate poisoning. In southern South America, these lesions are indistinguishable from those produced by Baccharis coridifolia, a toxic plant that contains macrocyclic trichothecenes, thus these conditions should be considered in the differential diagnosis of necrotizing lesions in alimentary and lymphoid organs.